Estudo teórico de propriedades do estado excitado de proteínas fluorescentes - Alves, Breno Xavier Porto (2024)
In this work, green fluorescent protein (GFP) was chosen as the object of study due to the photophysical characteristics of its chromophore in order to investigate excited state properties in biomolecular systems. Therefore, the goal was to obtain excitation energy data for the chromophore structures of the protein and the protein optimized at the PM6/Amber level using the ONIOM method, as well as representative structures from a 200 ns molecular dynamics trajectory. Single-point calculations were performed on these structures using the TD-DFT method, varying the functionals, basis sets, and the size of the layers treated with the ONIOM method. With the chosen functional and basis set, excitation energies were calculated for chromophores of fluorescent protein variants of GFP. Statistical analyses of RMSD and RMSF indicated structures with low fluctuations around the chromophore. The functionals that performed best were CAM-B3LYP and ωB97XD with the 6-311+G* basis set. The data obtained from TD-DFT calculations using the ONIOM approach are quite close to the values reported in the literature, showing significant variations for some structures arising from molecular dynamics. However, the average excitation energy values of the significant structures from each cluster of the molecular dynamics trajectory are closer to the experimental values. No significant influence of the protein on the energy levels of the GFP chromophore was observed. Regarding analogous chromophores, the excitation energies follow the trend of the literature, although the calculated values were overestimated compared to the experimental data.